Microcystic adnexal carcinoma: A focused review and updates - Nouran S. Hamed; Amor Khachemoune (Wolters Kluwer Medknow Publications, 2015)
Microcystic adnexal carcinoma (MAC) is an uncommon, locally aggressive, malignant cutaneous tumor with pilar and eccrine differentiation. In this article we describe the clinical presentation, pathologic hallmarks, and the use of new adjunct diagnostic devices, to optimize diagnosis, management and treatment options.